Laser Haemorrhoidoplasty versus Stapled Haemorrhoidopexy for Grade II–III Haemorrhoidal Disease: A Systematic Review and Meta-Analysis of Postoperative Pain and Perioperative Outcomes - Ricky Dwi Nur Tyastono; Muhammad Fahmi Salafuddin (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2026)
Background: Postoperative pain and delayed recovery are the principal drawbacks of excisional haemorrhoid surgery, and two minimally invasive alternatives — laser haemorrhoidoplasty (LH) and stapled haemorrhoidopexy (SH) — are increasingly used to overcome them. Although each has repeatedly been compared with conventional haemorrhoidectomy, the direct head-to-head evidence comparing LH with SH has never been pooled quantitatively. Objective: This systematic review and meta-analysis compared the perioperative, early postoperative pain and safety outcomes of LH and SH in adults with symptomatic haemorrhoidal disease. Methods: PubMed, Scopus-indexed journals, Crossref and Google Scholar were searched systematically for randomised and comparative studies directly comparing LH with SH. Ten studies were included and seven contributed poolable data. Random-effects models (DerSimonian–Laird, with Hartung–Knapp–Sidik–Jonkman intervals for inference on continuous outcomes) generated risk ratios (RR) for dichotomous outcomes and standardised mean differences (SMD, Hedges g) for continuous outcomes; raw mean differences were reported for interpretability. Risk of bias was appraised with RoB 2 and ROBINS-I, and the certainty of evidence was rated for each outcome. Results: Laser haemorrhoidoplasty was associated with a significantly shorter operative time (SMD −1.65, 95% CI −2.47 to −0.84; p<0.001; approximately 8 minutes shorter on average), a shorter hospital stay (SMD −3.07, 95% CI −5.58 to −0.55; p=0.017) and a non-significant trend toward less intraoperative blood loss (SMD −2.30, 95% CI −4.74 to 0.13; p=0.064). Early postoperative pain (≤24 h) did not differ significantly on pooling (SMD −0.66, 95% CI −1.95 to 0.63; p=0.32; I² 98%); this reflected a time-dependent crossover in which LH was less painful in the first hours but SH became less painful from 24 hours onward. Overall complications favoured LH numerically but not significantly (RR 0.58, 95% CI 0.25 to 1.30; p=0.18), an advantage confined to short-follow-up studies and reversed in the single 24-month trial. Recurrence, bleeding, anal stenosis and urinary retention were comparable. The certainty of evidence was low to very low for all outcomes. Conclusion: Laser haemorrhoidoplasty offered consistent intraoperative advantages over stapled haemorrhoidopexy, whereas early pain and safety were comparable and duration of follow-up was the dominant effect-modifier. Both are reasonable minimally invasive options; technique selection should be individualised pending adequately powered long-term trials.